The effects of fast neutrons on inoperable carcinoma of the stomach. Issue 2 (February 1975) - Catterall, M; Kingsley, D; Lawrence, G; Grainger, J; Spencer, J
Abstract : Thirty-nine unselected patients suffering from inoperable, recurrent, or residual adenocarcinoma of the stomach were referred for palliation with fast neutrons from the Medical Research Council's cyclotron at Hammersmith Hospital. A full course of 1440 rads given in 12 treatments over 26 days was administered to the patients. Because of the relatively low energy (7-5 MeV) of the beam from this particular machine, it was not possible to deliver the full dose uniformly throughout the tumour except in extremely thin patients. Pain, dysphagia, vomiting, and bleeding were relieved in the majority of cases. The side effects were minimal and easily controlled. Palpable masses disappeared. Five patients required surgery after neutron therapy. All the incisions were made through irradioated tissue and all except one healed normally. Tumour was present outside the treated area, but the absence of any palpable mass within the treated area was a consistent finding. Radiologically, the stomachs remained abnormal and later changes included gross mucosal abnormality and shrinkage. Fourteen patients came to necropsy and in 10 no tumour was present macroscopocally. Tumour cells were seen in all except two cases but these were few, surrounded by dense fibrous tissue, and may not have been viable. The remaining stomach was abnormal with a thickened wall and destruction of mucosa. Three of the four cases in which macroscopic tumour was present received less than the standard dose because of the inadequate penetration of the beam. Excellent regression of tumors was achieved by the neutrons, but the stomachs did not recover from this satisfactorily. Gastrectomy four to six months after treatment is therefore suggested. This operation and other surgical procedures in other patients were successfully carried out. There is a need for higher energy neutrons to improve treatment and extend it to patients of thick-set build.